1993
DOI: 10.1002/ajmg.1320480408
|View full text |Cite
|
Sign up to set email alerts
|

Association study of schizophrenia with dopamine D3 receptor gene polymorphisms: Probable effects of family history of schizophrenia?

Abstract: Using a case-control design, a reported association of schizophrenia with homozygosity at the dopamine D3 receptor gene locus was investigated in a group of patients (n = 53), with schizophrenia (DSM-III-R), and psychiatrically normal controls (n = 61), matched for ethnicity and area of residence. No significant differences in the distribution of alleles or genotypes between the two groups could be detected. However, among patients with a family history of schizophrenia, as compared to controls without such fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2
4

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 14 publications
2
29
2
4
Order By: Relevance
“…26,27 This observation would fit with complex models of aetiology for schizophrenia 3,34 which predict that those with a high familial loading are more likely to possess genetic risk factors. The present family-based study focuses upon this finding and attempts to demonstrate excess homozygosity in a sample of schizophrenics with at least one other affected first-degree relative.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…26,27 This observation would fit with complex models of aetiology for schizophrenia 3,34 which predict that those with a high familial loading are more likely to possess genetic risk factors. The present family-based study focuses upon this finding and attempts to demonstrate excess homozygosity in a sample of schizophrenics with at least one other affected first-degree relative.…”
Section: Introductionmentioning
confidence: 77%
“…Two further studies found excess homozygosity in two of these sub-groups. Nimgaonkar and colleagues 27 found a strong effect in those patients with a family history of schizophrenia and Jonssen et al 28 found increased levels of homozygosity in schizophrenics with a good response to neuroleptics. Nimgaonkar et al 29 also found a significant excess of allele 1 homozygotes in a population of Afro-American patients.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with two previous studies, 17,20 although not always replicated. 18,[21][22][23][24][25][26] The various criteria used to define treatment efficacy in these previous reports could at least partly explain the discrepancies. Definition of treatment response can rely on persistence of positive or negative symptoms, percentage of improvement on symptomatic scales, ability for reinsertion and/or election for clozapine therapy; leading to distinct clinical subgroups, whose relevance with regard to underlying physiopathological processes is questionable.…”
Section: Genotypesmentioning
confidence: 99%
“…10 Extending the sample size, the association was found to be most marked in schizophrenic males, those with family history and in good responders to antipsychotic drugs. 11,12 In independent samples of patients and controls, Nimgaonkar et al 13,14 suggested an association with allele 1 and Shaikh et al 15 likewise showed an association with allele 1. In contrast, Kennedy et al 16 showed a higher frequency of allele 2 and genotype 2-2 in their patients and most recently Ebstein et al 17 found the allele 2 and the genotype 2-2 to be significantly associated with the disease in a combined sample of Italian, Ashkenazi and non-Ashkenazi Jews.…”
Section: Introductionmentioning
confidence: 97%